2000
DOI: 10.1161/01.cir.102.4.438
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Blood Flow and Myocardial Uptake of 201 Tl and 99m Tc-Sestamibi During Coronary Vasodilation Induced by CGS-21680, a Selective Adenosine A 2A Receptor Agonist

Abstract: CGS-21680 elicits coronary vasodilation comparable to that of adenosine and produces profound heterogeneity of MBF and of (201)Tl and (99m)Tc-sestamibi myocardial uptake, rendering it a promising agent for pharmacological myocardial perfusion imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The increase in normal-zone regional myocardial blood flow after a 1.0 g/kg bolus of ATL-146e was greater than the increase in normal-zone flow reported after either MRE-0470 or CGS-21680 infusions. 10,11 MAP fell only slightly after an ATL-146e bolus, such that it remained Ͼ90 mm Hg. This result is in marked contrast to adenosine bolus injections that caused MAP to fall precipitously by Ϸ50 mm Hg.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…The increase in normal-zone regional myocardial blood flow after a 1.0 g/kg bolus of ATL-146e was greater than the increase in normal-zone flow reported after either MRE-0470 or CGS-21680 infusions. 10,11 MAP fell only slightly after an ATL-146e bolus, such that it remained Ͼ90 mm Hg. This result is in marked contrast to adenosine bolus injections that caused MAP to fall precipitously by Ϸ50 mm Hg.…”
mentioning
confidence: 90%
“…) and CGS-21680 (0.5 to 4.0 g · kg Ϫ1 · min Ϫ1 ), 10,11 yet the former produced a nearly equivalent increase in CF. Thus, ATL-193 is more potent than both MRE-0470 and CGS-21680, and these findings are in agreement with what would be predicted on the basis of the in vitro radioligand binding assay data.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In animal studies, vasodilators in the setting of severe coronary stenoses have been shown to create changes in the endocardial-epicardial flow ratio which could result in ischemic ECG changes in those with normal perfusion. 26 Recently, Sharma and colleagues demonstrated a very low incidence of hard events (CD or MI) in patients with normal MPI and adenosine-induced ischemic ECG changes. 15 Similar to the patient population in the study by Hage, Sharma et al also excluded patients with known CAD.…”
Section: Prognostic Significance Of Vasodilator Stress Ecg Changesmentioning
confidence: 99%
“…Apadenoson and CGS-21680 have been investigated in preclinical trials. To date, there are limited data published for binodenoson (25)(26)(27)(28)(29)(30) and even fewer for apadenoson and CGS-21680 (31,32).…”
Section: A 2a Receptor Agonistsmentioning
confidence: 99%